2020
DOI: 10.1029/2019ja027370
|View full text |Cite
|
Sign up to set email alerts
|

Multiharmonic Toroidal Standing Alfvén Waves in the Midnight Sector Observed During a Geomagnetically Quiet Period

Abstract: Multiharmonic toroidal standing Alfvén waves were detected in the midnight sector of the plasmasphere.• The source of the waves are considered to be ultralow frequency waves generated in the ion foreshock.• The toroidal waves were not detected on the ground at stations located in the midnight sector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 86 publications
3
18
0
Order By: Relevance
“…The observed discrete wave frequencies are consistent with the excitation of only odd harmonic mode standing FLRs, as validated by modeling which solves the guided toroidal Alfvén wave equation in a dipole field with plasma mass density along the field lines constrained by the IRI model. These waves appear similar to the odd harmonic mode standing guided toroidal waves detected by Van Allen probe B, recently reported on by Takahashi et al (2020). However, those waves occurred at much higher L-shells between dipole L-values of 4.2 and 6.1, as is commonly observed.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The observed discrete wave frequencies are consistent with the excitation of only odd harmonic mode standing FLRs, as validated by modeling which solves the guided toroidal Alfvén wave equation in a dipole field with plasma mass density along the field lines constrained by the IRI model. These waves appear similar to the odd harmonic mode standing guided toroidal waves detected by Van Allen probe B, recently reported on by Takahashi et al (2020). However, those waves occurred at much higher L-shells between dipole L-values of 4.2 and 6.1, as is commonly observed.…”
Section: Discussionsupporting
confidence: 86%
“…These waves appear similar to the odd harmonic mode standing guided toroidal waves detected by Van Allen probe B, recently reported on by Takahashi et al. (2020). However, those waves occurred at much higher L‐shells between dipole L ‐values of 4.2 and 6.1, as is commonly observed.…”
Section: Discussionsupporting
confidence: 85%
“…The waves are detected at a high rate on the dayside from L 6 to L 12 (spacecraft apogee). The rate becomes low on the nightside, but toroidal waves are still detected there along with Pi2 pulsations, most often after substorm onsets (Takahashi et al, 1988;Takahashi et al, 2018) and when ULF waves generated in the ion foreshock penetrate deep into the magnetosphere (Takahashi et al, 2020). The presence of substorm-related toroidal waves is evident in Figure 10B as a region of large δV ϕ amplitudes in the premidnight sector.…”
Section: Global Modelsmentioning
confidence: 95%
“…Because the AE index had moderate values (<200 nT) during the wave event in this example, we expect that nightside Pi2 waves and toroidal waves are commonly excited and can be easily detected off the magnetic equator in association with small substorms or other minor disturbances in the magnetotail. Because it appears difficult to determine nightside toroidal wave frequencies with ground magnetometers (Takahashi et al, 2020), we expect that a model derived using spacecraft data will perform better on the nightside than models derived using only ground data.…”
Section: Global Modelsmentioning
confidence: 99%
“…After sunset, the conductivity decreases and in particular, situations one or both ends of the field line should be theoretically considered free [58]. However, a recent study by Takahashi et al [59] interpreted resonances observed in the midnight sector as fix-end modes, suggesting that even during nighttime, the ionospheric condition could sustain normal modes. FLRs can be used to remotely sense the equatorial plasma mass density in the inner magnetosphere and led the scientific community to set up large meridional arrays of magnetometers such as the Mid-continent MAgnetoseismic Chain (McMAC, [60]) and the Canadian Array for Realtime InvestigationS of Magnetic Activity (CARISMA, [61]) in North America, which, when combined, provide magnetic field data from L = 1.2 to 11 at the same local time (≈UT − 6.5 h).…”
Section: Observation Of Field Line Resonancesmentioning
confidence: 99%